THE INFLUENCE OF ETHNIC COMMUNICATION ON THE NATIONAL IDENTITY AND THE STATE FOREIGN POLICY - O. A. Ignatjeva (Концепт: философия, религия, культура, 2017)
The current article presents the quintessence of Max Weber’s ideas regarding the state opportunity to take a leading position on the global stage. The classic of sociology was not only the cabinet scientist but the practice politician. He took part in the Versailles Conference on the results of the First World War and was one of the authors of the Constitution of the Weimar Republic. His ideas about Parliament and Reich President were reflected in the Constitution of the Federal Republic of Germany. All his life the scientist worked out a way of returning the former greatness to Germany that had just been joined by Otto von Bismarck. The author considers, that the writings of Max Weber afford an opportunity to answer the question crucial for the Russian Federation: «How to take the leading positions in the modern globalizing world»? The researcher, guided by the works of German classic, offers to pay attention to one of the aspects that plays a significant role in the strong state building: the formation of the unified national identity. The solid nation, built on the centuries-old ethnic communication, can be the reliable foreign policy tool if the interests of the nation and the state coincide. The current conception is being considered in the context of the experience of Great Britain as the center of the Commonwealth, the Federal Republic of Germany as the leader of the European Union and Russia. The research is theoretic using systematic, hermeneutic, comparative and historical genetic methods. The current article presents the stages of national identity formation in Great Britain, Germany and Russia taking into account the peculiar features of intercultural communication between the ethnos living in these countries. This paper presents a detailed analysis of the unified nation’s influence on the applicability of state leaders’ attractive and unattractive ideas in the foreign policy. The article refers to the materials from the author’s dissertation «The heuristic potential of Max Weber’s conception of political power», defended in 2012 in the faculty of sociology of St. Petersburg State University